Mental workload in aviation: an investigation of physiological and qualitative assessment methods - Prasetyo, Ridwan Aji Budi (2022)
Flying is a safety critical activity in which the ability of the pilot to synthesise multiple sources of information, make decisions and produce appropriate control inputs is critical. Consequently, understanding and managing pilots’ mental workload (MWL) is critical to flying safely and in the design of flight-decks and procedures. Investigation of objective ways to measure MWL is necessary as recent advances in sensing technology offer new opportunities to develop assessment methods that are less intrusive than existing techniques. For example, physiological methods are emerging as options for MWL assessment as they can provide in-situ measurement. These methods have potential advantages in terms of being relatively less intrusive than traditional methods, offering benefits for real workplace settings, including in the cockpit. The research presented in this thesis focuses on the exploration of MWL measurement during a simulated flying task through the investigation of factors influencing MWL during flight and the utility of using more objective methods for evaluating it.